Determinants of disease course and severity in hyperemesis gravidarum. (February 2020) - Koot, Marjette H.; Grooten, Iris J.; van der Post, Joris A.M.; Bais, Joke M.J.; Ris-Stalpers, Carrie; Leeflang, Mariska M.G.; Bremer, Henk A.; van der Ham, David P.; Heidema, Wieteke M.; Huisjes, Anjoke; Kleiverda, Gunilla; Kuppens, Simone M.; et al.
Abstract: Objective: We aimed to identify determinants that predict hyperemesis gravidarum (HG) disease course and severity. Study design: For this study, we combined data of the Maternal and Offspring outcomes after Treatment of HyperEmesis by Refeeding (MOTHER) randomized controlled trial (RCT) and its associated observational cohort with non-randomised patients. Between October 2013 and March 2016, in 19 hospitals in the Netherlands, women hospitalised for HG were approached for study participation. In total, 215 pregnant women provided consent for participation. We excluded women enrolled during a readmission (n = 24). Determinants were defined as patient characteristics and clinical features, available to clinicians at first hospital admission. Patient characteristics included i.e. age, ethnicity, socio-economic status, history of mental health disease and HG and gravidity. Clinical features included weight loss compared to pre-pregnancy weight and symptom severity measured with Pregnancy Unique Quantification of Emesis (PUQE-24) questionnaire and the Nausea and Vomiting in Pregnancy specific Quality of Life questionnaire (NVPQoL). Outcome measures were measures of HG disease severity present at 1 week after hospital admission, including weight change, PUQE-24 and NVPQoL scores. Total days of admission hospital admission and readmission were also considered outcome measures. Results: We found that high PUQE-24 and NVPQoL scores at hospital admission were associated with those 1 week after hospital admission (difference ( β ) 0.36, 95 %CI 0.16 to 0.57 and 0.70, 95 %CI 0.45–1.1). PUQE-24 and NVPQoL scores were not associated with other outcome measures. None of the patient characteristics were associated with any of the outcome measures. Conclusion: Our findings suggest that the PUQE-24 and NVPQoL questionnaires can identify women that maintain high symptom scores a week after admission, but that patient characteristics cannot be used as determinants of HG disease course and severity.